Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3349/ymj.2022.63.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Da Vinci SP Single-Port Robotic Surgery in Gynecologic Tumors: Single Surgeon’s Initial Experience with 100 Cases

Abstract: Purpose To report preliminary experience of single-port robotic surgery using the da Vinci SP surgical system in gynecologic tumors. Materials and Methods This was a retrospective study on 100 consecutive patients who underwent da Vinci SP single-port robotic surgery between November 2018 and January 2021. All procedures were performed by an experienced gynecologic surgeon using a single 2.5-cm umbilical incision. Results Of the 100 cases, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Further, the surgeon can perform multi-quadrant surgery without repositioning the operating room table and almost no clashing of the instruments. Similar favourable ergonomics, positioning and outcomes have been reported using SP robotics in thoracic, hernia, gynaecological and urological surgery[38][39][40][41].This work adds to the literature as there are few reports of SP robotic CRS. All published work has very small numbers with no follow-up, showing only initial safety and feasibility.…”
supporting
confidence: 72%
“…Further, the surgeon can perform multi-quadrant surgery without repositioning the operating room table and almost no clashing of the instruments. Similar favourable ergonomics, positioning and outcomes have been reported using SP robotics in thoracic, hernia, gynaecological and urological surgery[38][39][40][41].This work adds to the literature as there are few reports of SP robotic CRS. All published work has very small numbers with no follow-up, showing only initial safety and feasibility.…”
supporting
confidence: 72%
“…Preclinical studies have used the SS platform to perform a variety of gynecological surgeries in porcine and cadaveric models using an umbilical approach [68]. The clinical studies showed the feasibility, safety, and effectiveness of the SS and SP® platforms in the performance of a wider variety of benign and malignant gynecological procedures, enrolling an increasing number of patients [69][70][71][72][73][74][75][76][77][78].…”
Section: Single-incision Robotic Platformsmentioning
confidence: 99%
“…The introduction of bipolar instruments [71], wristed needle drivers [79], and SS ports able to accommodate the SP® cannula, and three other laparoscopic instruments at the same time represented improvements [78]. Important studies comparing SS against Multi-port and SS against SP® showed less post-operative pain, comparable surgical outcomes, shorter postoperative hospital discharge, cost reduction in surgical instruments, total hospitalization cost, and higher patient satisfaction [80][81][82].…”
Section: Single-incision Robotic Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its dualjointed robotic instruments enable freedom of movements within more con ned space, and works hand in hand with the all-improved endoscopic camera [10,11]. Da Vinci SP technology is widely incorporated in urology [10] and benign gynecology [11,12], with no study of its application in gynecologic oncology speci cally for cervical cancer till date. The study aimed to present the rst clinical experience and surgical outcome of robotic surgery with da Vinci SP for cervical cancer stage IA-IB.…”
Section: Introductionmentioning
confidence: 99%